A novel fluorescence strategy for mercury ion and trypsin activity assay based on nitrogen-doped graphene quantum dots. (27th September 2018) - Su, Dandan; Wang, Mengke; Liu, Qing; Qu, Zhengyi; Su, Xingguang
Abstract : Fluorescent detection of Hg 2+ and trypsin based on trypsin-modulated competition between Hg 2+, N-GQDs and HSA. Abstract : In this paper, we developed a simple, convenient and sensitive fluorescent probe for mercury ions (Hg 2+ ) and trypsin activity assay based on nitrogen-doped graphene quantum dots (N-GQDs). Hg 2+ can quench the fluorescence of N-GQDs due to electron transfer from N-GQDs to Hg 2+ . However, amino acids or peptide fragments formed by hydrolysis of human serum albumin (HSA) in the presence of trypsin have a stronger affinity for Hg 2+, thus the fluorescence of N-GQDs will be recovered after the addition of HSA and trypsin. Hg 2+ and trypsin activity could be monitored via the change of fluorescence intensity of the N-GQDs. Under optimal conditions, the fluorescence intensity of N-GQDs was proportional to the concentration of Hg 2+ and trypsin in the range of 0.02–1 μM and 0.03–8 μg mL −1 with a limit of 0.0047 μM and 0.0063 μg mL −1, respectively. Besides, soybean trypsin inhibitor (SBTI) as a model for trypsin inhibition was used to confirm the feasibility of the system and the value of IC50 is 1.31 μg mL −1 . The proposed method was successfully applied to the determination of Hg 2+ and trypsin activity in real samples with satisfactory results.